The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphar.2019.00970
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Puumala orthohantavirus Strains in the Northwestern Region of the Republic of Tatarstan in Relation to the Clinical Manifestations in Hemorrhagic Fever With Renal Syndrome Patients

Abstract: Over 1,000 cases of hemorrhagic fever with renal syndrome (HFRS) were recorded in the Republic of Tatarstan (RT) in 2015. HFRS is a zoonotic disease caused by several different Old World hantaviruses. In RT, Puumala orthohantavirus (PUUV) is a prevalent etiological agent of HFRS. We looked for the genetic link between the PUUV strains isolated from the bank voles and from the infected humans. In addition, possible correlation between the genetic makeup of the PUUV strain involved and different clinical picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…We therefore identified PUUV as the causative infectious agent of NE from the RT and the RM. These data support previous observations that PUUV is the prevalent etiological agent of NE in the Volga Federal District [38,40,41], which includes the RT, the RM, the RB, and Udmurtia. Therefore, we suggest that differences in cytokine activation in NE from the RT and the RM could be explained by host immune response mechanisms to viral infection.…”
Section: Resultssupporting
confidence: 91%
“…We therefore identified PUUV as the causative infectious agent of NE from the RT and the RM. These data support previous observations that PUUV is the prevalent etiological agent of NE in the Volga Federal District [38,40,41], which includes the RT, the RM, the RB, and Udmurtia. Therefore, we suggest that differences in cytokine activation in NE from the RT and the RM could be explained by host immune response mechanisms to viral infection.…”
Section: Resultssupporting
confidence: 91%
“…PUUV strains from cluster A and the subclades' Northwest of RT', including strains circulating in the bank vole populations west and north of Kazan [17], appear genetically distant, although the geographical distance between these areas is in the range of 20-70 km. This suggests that a group of strains in the North-West of RT was also formed as a result of a separate migration wave of bank voles.…”
Section: Clustermentioning
confidence: 96%
“…In the previous investigations, we have performed a comparative analysis of partial S and M segment sequences of the PUUV strains circulating in the Pre-Kama and Trans-Kama area and have demonstrated a significant variation of PUUV strains' genome in the RT [15,16]. It has been shown that the PUUV strains in the bank voles from Zelenodolsky and Vysokogorsky districts diverged significantly from the virus strains found in Laishevsky and Pestrechinsky districts [17]. The current study aims to analyze the genetic variability of PUUV in the Pre-Kama region.…”
Section: Introductionmentioning
confidence: 99%
“…NE is endemic in the republic of Tatarstan, Russia [16]. We have previously demonstrated that Puumala orthohantavirus (PUUV) is the primary cause of NE in Tatarstan [17]. It is believed that endothelial cells are the primary targets of PUUV, where the virus can replicate without a cytopathic effect [18].…”
Section: Introductionmentioning
confidence: 99%